From Conventional Practice to Immersive Simulation: A Systematic Literature Review on Virtual Professional Makeup as Transformative Learning Media - Iut Nuraini; Ria Andriani Mukti; Fitria Hansyah Fatmasari; Quienera Putra Joshua (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
Innovative technologies have expanded across various fields of vocational education, including the use of immersive technologies in legal education for soft skills development and virtual clinical simulations in nursing education. However, the application of immersive technologies in creative professions, including cosmetology education, remains relatively limited. This study aims to explore the pedagogical benefits of immersive virtual simulations in supporting the development of professional skills in makeup and beauty education. This research employs a systematic literature review based on PRISMA 2020 criteria, analyzing a total of 32 peer-reviewed articles published between 2016 and 2026. The findings indicate that immersive simulations, such as virtual reality (VR), augmented reality (AR), and interactive 3D environments, can enhance psychomotor skills, learner engagement, intrinsic motivation, and professional confidence. These improvements are particularly evident in structured vocational fields such as nursing, engineering, and technical education, where measurable gains in procedural accuracy and cognitive engagement have been observed. However, the literature also shows that the mere presence of technology does not guarantee learning effectiveness. Pedagogical factors such as interactivity, sense of presence, quality of feedback, simulation fidelity, and cognitive load management play a crucial role in determining learning success. Furthermore, studies specifically addressing professional cosmetology education remain very limited. Overall, immersive learning has significant potential to transform vocational education systems into more flexible and learner-centered environments.